Testing Rationality in Contingent Valuation Studies - Cunha-e-Sá, Maria A. (2019)
In a world characterized by one unrationed good (ie, market good), and one rationed, such as most of environmental goods, we obtain sufficient conditions for the existence of an underlying rational preference structure based on a system of mixed demand functions. The implications for CV studies are derived. For policy purposes, in particular in what concerns welfare evaluations, our results can be of great relevance.